Breeding report of a new small-sized colored flesh watermelon cultivar Zhongli 20 with high-quality and storage resistance - ZHOU Dan; SHANG Jianli; MA Shuangwu; LI Na (Guoshu xuebao, 2025)
Zhongli 20 is a new small-sized colored-flesh watermelon selected from a cross between a red-fleshed watermelon 19F22 and a yellow-fleshed watermelon 19F09. The entire growth period was about 95 days, and the fruit growth period was about 30 days. The male and female plants are monoecious, with the first female flower on 7th nodes and the male flower on 4th nodes. The fruit was oval shape, with light green rinds covered in dark stripes. The average weight of single fruit could reach over 2 kg. The flesh was yellow-red inlaid, commonly known as rainbow flesh. The soluble solid content of the center flesh was about 14% and 11% of the edge. The flesh was delicate, crispy, and fruity flavored. The variety comparison experiments were conducted in Zhengzhou, Xinxiang, Xuchang in Henan Province from 2020 to 2021, with the control variety of L600. The field trails were conducted with hanging vine cultivation and double vine pruning. The performance of Zhongli in terms of the single fruit weight, content of soluble solid content, yield, storability, transportability and portability was much better than that of the control. It had tolerance to low temperature and weak light and general heat tolerance during fruit ripening, but no resistance to wilt and viral diseases. It would be more adapted for early spring planting in protected cultivation facilities, and more suitable for hanging vine cultivation, with single vine pruning, maintaining one fruit per plant, the recommended planting density woud be 1800 plants per 666.7 m2. Zhongli 20 was registered as a non-major crop variety by the Ministry of Agriculture and Rural Affairs in 2024.